Sumber Daya Manusia (SDM) pada Swalayan Aneka Jaya Demak: Kunci Keberhasilan dalam Pelayanan dan Produktivitas Usaha - Dewi Sulistiowati; Henry Yuliamir (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to analyze human resource management (HRM) as a key factor in improving service quality and business productivity at Aneka Jaya Supermarket Demak. The research focuses on recruitment and selection processes, employee training and development systems, and the main challenges faced in HRM practices. The study applies a qualitative approach using data collected through in-depth interviews, observations, and documentation. The data were analyzed descriptively by identifying patterns, themes, and relationships emerging from field findings. The results show that recruitment and selection are carried out in a simple manner, emphasizing honesty, discipline, and teamwork, without a standardized competency assessment system. Employee training is conducted through on-the-job learning, focusing on basic customer service skills and product arrangement. The main obstacles include high employee turnover, limited training budgets, and the absence of a continuous performance evaluation system. Nevertheless, management addresses these challenges through effective internal communication, simple reward programs, and fostering a family-oriented work environment. Overall, this research highlights that the success of HRM at Aneka Jaya Supermarket Demak depends on maintaining a balance between a humanistic personal approach and an adaptive management system to navigate the dynamics of the local retail industry.